Gambaran temporomandibular disorders pada lansia di kecamatan wanea - Gabrila, Johannis; Tendean, Lydia; Zuliari, Kustina (e-GiGi, 2016)
Abstarct: Elderly was the final phase of the development of human life. The elderly will experience a reduction of posterior or anterior teeth, degeneration, thinning of the oral mucosa, hyposalivation, decreased activity and muscle mass, setbacks of many body functions including temporomandibular joint (TMJ) function. Arthritis and osteoporosis that occur in TMJ due to excessive load as well as tooth loss lead to temporomandibular disorders (TMD). Elderly who has TMD will experience discomfort in eating and drinking. This study aimed to obtain the description of TMD among the elderly at Wanea district. This was a descriptive study with a cross sectional design conducted in June 2016. Samples were obtained by using purposive sampling. The elderly were interviewed by using the Fonseca's questionnaire and were checked for clicking sound and teeth loss. The results showed that of 98 respondents, there were 54 elderly with mild TMD, 12 elderly with moderate TMD, and 5 elderly with severe TMD; 28 elderly had no TMD. Clicking sound was found in 70 elderly, partial tooth loss in 78 ederly, and whole tooth loss in 20 ederly. Conclusion: Most elderly in Wanea had TMD. The most frequent that had TMD was age 60-70 years old and females. The most common classification of TMD was mild TMD.Keywords: elderly, temporomandibular disorders.Abstrak: Lanjut usia (Lansia) merupakan tahap akhir perkembangan dari kehidupan manusia. Lansia umumnya mengalami pengurangan jumlah gigi geligi posterior maupun anterior, terjadi degenerasi, penipisan mukosa oral, hiposalivasi, penurunan aktivitas dan massa otot, serta terjadi kemunduran banyak fungsi tubuh termasuk fungsi sendi temporomandibular (TMJ). Artritis dan osteoporosis yang dapat terjadi pada TMJ akibat beban berlebihan serta kehilangan gigi pada lansia mengakibatkan terjadinya temporomandibular disorders (TMD). Lansia yang mengalami TMD akan mengalami ketidaknyamanan dalam hal makan dan minum. Penelitian ini bertujuan untuk mengetahui gambaran TMD pada lansia di Kecamatan Wanea dan dilaksanakan pada bulan Juni 2016. Jenis penelitian ialah deskriptif dengan desain potong lintang. Pengambilan sampel menggunakan purposive sampling. Pada penelitian ini dilakukan wawancara pada lansia menggunakan Fonseca’s Questionnaire, serta pemeriksaan bunyi clicking dan pemeriksaan kehilangan gigi. Hasil penelitian mendapatkan dari 98 responden, 54 lansia mengalami TMD ringan, 12 lansia TMD sedang, 5 lansia TMD berat; 28 lansia tanpa TMD. Bunyi clicking terdapat pada 70 lansia, kehilangan gigi sebagian sebanyak 78 lansia, dan kehilangan gigi seluruhnya sebanyak 20 lansia. Simpulan: Sebagian besar lansia di Kecamatan Wanea mengalami TMD. Yang tersering ditemukan ialah kelompok usia 60-70 tahun, jenis kelamin perempuan dan klasifikasi TMD ringan.Kata kunci: lansia, temporomandibular disorders